Early treatment of condylar hyperplasia with high condylectomy (Research, Society and Development, 2020)
Condylar hyperplasia (CH) is characterized by an excessive growth of the mandibular condyle causing esthetic and functional problems. The treatment of CH is still not a consensus in the literature, and it is possible to find several surgical management protocols. Therefore, this study aims to report the early surgical treatment of CH through a descriptive, qualitative, case report type. Male patient, 13 years old, with a history of severe facial asymmetry. Physical examination revealed asymmetry in the lower third of the face, contralateral deviation of the chin, inclination of the occlusal plane and malocclusion. The tomographic examination showed hyperplasia in the left condylar region, with lengthening of the condylar process, enlargement of the ipsilateral mandibular body and contralateral deviation of the chin. The surgical procedure for high condylectomy through pre-auricular access was performed with a 7 mm resection of the left condylar process. An outpatient patient, more than two years after the procedure, presented facial symmetry, good mouth opening, stable occlusion and absence of pain complaints. Thus, high condylectomy can be considered a rational alternative for early treatment in cases of active CH at the beginning of puberty, reducing the growth stimulus of the affected condyle and reducing the need for posterior orthognathic surgery.